Water permeable brick prepared by curing Yellow River sediment through waste residue alkali-activated material and preparation method of water permeable brick
By using waste residue alkali-activated materials to solidify Yellow River sediment to prepare double-layer permeable bricks, the problems of high energy consumption and high cost in permeable brick production have been solved, and the permeability and durability have been improved, promoting the recycling of solid waste resources.
Patent Information
- Application Number
- CN202511110942.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-07
AI Technical Summary
Existing permeable brick production methods are characterized by high energy consumption, high cost, and poor durability. Natural river sand resources are depleted, industrial solid waste utilization is low, and the sediment deposited in the Yellow River has not been effectively utilized.
Waste residue alkali-activated material is used to solidify Yellow River sediment and prepare double-layer permeable bricks. The upper layer has small pores to prevent clogging, while the lower layer has large pores to accelerate water flow. Coal gangue manufactured sand and bauxite tailings are used to replace natural raw materials, and hydrogels and cellulose ethers are added to improve performance.
It enables low-cost, low-energy production of permeable bricks, improves permeability and crack resistance, and has good mechanical properties and environmental advantages, making it suitable for sponge city construction.
Smart Images

Figure BDA0005539847390000071 
Figure BDA0005539847390000081
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of solid waste resource utilization, in particular to a waste residue alkali-activated material solidified Yellow River sediment water permeable brick and a preparation method thereof. BACKGROUND
[0002] Under the new situation that natural resources are facing exhaustion and people's environmental awareness is gradually increasing, modernization construction pays more and more attention to the organic combination of green new technology and environment, humanity and other factors. The "sponge city" is an important form of green low-carbon and smart construction, which can reduce the damage of urban construction to natural hydrological ecological environment to the greatest extent. In the process of sponge city construction, the water permeability of the road plays a crucial role. The research and application of water permeable bricks are also increasing. The water permeable bricks developed in China at present are mainly divided into two categories: (1) building waste and industrial solid waste as raw materials, high-temperature sintering forming water permeable brick; (2) cement, epoxy resin and other inorganic and organic binders are used to cement gravel and silica sand aggregate, and the water permeable brick is formed by normal temperature pouring. Although many research results have been achieved at present, there are still many problems to be solved. The sintering forming has high energy consumption, and the requirements for production equipment and process are also high. The cost of normal temperature pouring using cement and resin binders is high, and the high molecular binder is easy to age and has poor durability.
[0003] The Yellow River is famous for its high sediment, and a large amount of sediment accumulation can easily cause flood disasters, threatening people's life and health and property safety. Using the Yellow River sediment as a building material can effectively alleviate the problem of suspended river in the lower reaches and reduce the phenomenon of random mining and destruction of ecology of clay, sand and other materials.
[0004] Coal gangue is an industrial solid waste discharged in the process of coal mining and washing. Under the background of actively promoting waste utilization, energy saving and emission reduction in China, the comprehensive utilization of coal gangue has been gradually valued. Using coal gangue to make sand to replace natural river sand is one of the important ways of comprehensive utilization of coal gangue. Compared with natural river sand, coal gangue sand has simple and controllable composition, which is basically consistent with the composition of the sand raw material, has good adhesion, strong compressive strength, longer service life and broad application prospect.
[0005] Bauxite tailings are low-quality ores produced in the beneficiation process of alumina production industry. They are generally used for the preparation of refractory materials, artificial stone and low-temperature ceramic wood, etc. Because the mineral components in the aluminum tailings are stable in performance, not easy to hydrolyze or weather, and do not contain excessive harmful components that can destroy the stability of cement and affect the strength of the structure, they can also be used to replace natural raw materials such as fine sand and gravel.
[0006] Therefore, under the premise of ensuring the performance of the water permeable brick, if the above solid waste materials are used as cementing materials and aggregates and solidified and formed at normal temperature, great environmental and economic benefits can be brought. SUMMARY
[0007] In order to promote the resource utilization of the Yellow River silt and other solid waste materials, the application provides a waste residue alkali-activated material solidified Yellow River silt water permeable brick and a preparation method thereof. By fully exerting the synergistic effect of various types of industrial waste residues and the potential advantages of the Yellow River silt, a double-layer non-burned water permeable brick is prepared. The upper layer has small pores to prevent blockage, and the lower layer has large pores to accelerate water flow. The process is simple, energy-saving, cost-saving, and easy to popularize and apply in practical engineering.
[0008] In order to achieve the above-mentioned purpose, the application provides a waste residue alkali-activated material solidified Yellow River silt water permeable brick. The waste residue alkali-activated material solidified Yellow River silt water permeable brick is a double-layer non-burned water permeable brick, which comprises an upper layer water permeable brick and a lower layer water permeable brick with inconsistent pores. The void of the upper layer water permeable brick is smaller than that of the lower layer water permeable brick. Both the upper layer water permeable brick and the lower layer water permeable brick contain waste residue alkali-activated material and Yellow River silt.
[0009] Preferably, the raw materials and their mass percentages of the upper layer water permeable brick are as follows: waste residue alkali-activated material 15% to 25%, Yellow River silt 10% to 20%, coal gangue machine-made sand 45% to 65%, and water gel 5% to 10%.
[0010] Preferably, the upper layer water permeable brick additionally contains water reducing agent with a mass percentage of 0.15% to 0.20% and water with a mass percentage of 7% to 15%.
[0011] Preferably, the raw materials and their mass percentages of the lower layer water permeable brick are as follows: waste residue alkali-activated material 15% to 30%, Yellow River silt 10% to 20%, and bauxite tailings 50% to 75%.
[0012] Preferably, the lower layer water permeable brick additionally contains cellulose ether with a mass percentage of 0.05% to 0.2% and water with a mass percentage of 7% to 15%.
[0013] Preferably, the waste residue alkali-activated material is prepared by mixing the following raw materials in the following mass percentages: 35 to 45% of slag cement, 20 to 35% of red mud, 25 to 35% of fly ash, 0.02 to 0.06% of sodium hydroxide, and 0.02 to 0.06% of sodium silicate.
[0014] Preferably, the particle size range of the Yellow River silt is 0.005mm to 0.5mm, and the mass concentration of heavy metal dissolved in the silt is lower than the national soil environmental quality standard GB15618.
[0015] Preferably, the particle size range of the coal gangue machine-made sand is 1.0mm to 2.5mm.
[0016] Preferably, the aggregate particle size of the bauxite tailings is 4.75mm-9.5mm.
[0017] The application also provides a preparation method of the waste residue alkali-activated material solidified Yellow River sediment water permeable brick.
[0018] (1) Preparation of the mixing material of the upper layer water permeable brick: the waste residue alkali-activated material, the Yellow River sediment, the coal gangue machine-made sand, the water reducing agent and the hydrogel are weighed according to the proportion, put into a mixer and mixed uniformly, then water is added and continuously mixed uniformly to obtain the mixing material of the upper layer water permeable brick.
[0019] (2) Preparation of the mixing material of the lower layer water permeable brick: the waste residue alkali-activated material, the Yellow River sediment and the cellulose ether are mixed uniformly by dry mixing, then the bauxite tailings are added and continuously mixed until uniform, and finally water is added and mixed uniformly to obtain the mixing material of the lower layer water permeable brick.
[0020] (3) Waste residue alkali-activated material solidified Yellow River sediment water permeable brick: the upper layer mixing material is first loaded into a mold and vibrated and compacted; then the lower layer mixing material is continuously poured into the mold to fill the entire mold and vibrated and compacted; wherein the filling volume ratio of the mixing material of the upper layer water permeable brick to the mixing material of the lower layer water permeable brick is 1:3; finally, the test piece with the mold is placed in an environment with a temperature of 20±2℃ and a relative humidity of 98% for 1d, then the mold is removed, and the test piece is taken out after being continuously cured to the corresponding age according to the actual needs.
[0021] Therefore, the application has the following beneficial effects:
[0022] The application uses industrial waste residues such as red mud and fly ash to prepare cementing materials, uses coal gangue, tailings and Yellow River sediment as aggregates, realizes the recycling of solid waste resources, has the advantages of energy saving, consumption reduction, low carbon and environmental protection, and reduces the production cost of the water permeable brick. The incorporation of the hydrogel improves the water absorption and water retention capacity of the upper layer structure of the water permeable brick, can make the water permeable brick quickly absorb surface water, and effectively prevent the brick from efflorescence; on the other hand, the incorporation of the hydrogel reduces the elastic modulus of the upper layer structure of the water permeable brick and enhances the crack resistance thereof. The incorporation of the cellulose ether is beneficial to accelerating the water absorption of the upper layer structure and improves the water retention performance of the lower layer structure of the water permeable brick, gives the brick the self-regulating function of wet water absorption and dry water permeation, and effectively reduces the risk of dry shrinkage cracking of the water permeable brick. In summary, the preparation process of the water permeable brick is simple, the cost is low, the application range is wide, and the water permeable brick has good practical application value.
[0023] The technical solutions of the application are further described in detail through examples. DETAILED DESCRIPTION
[0024] Unless otherwise defined, the technical terms or scientific terms used in the application shall have the usual meanings understood by those skilled in the art.
[0025] The application provides a waste residue alkali-activated material solidified Yellow River sediment water permeable brick.
[0026] The raw materials and their mass percentages of the upper layer water permeable brick are as follows: 15-25% of waste residue alkali-activated material, 10-20% of Yellow River sediment, 45-65% of coal gangue machine-made sand and 5-10% of water gel, the sum of the above raw materials is 100%, and 0.15-0.20% of water reducing agent and 7-15% of water are additionally added.
[0027] The raw materials and their mass percentages of the lower layer water permeable brick are as follows: 15-30% of waste residue alkali-activated material, 10-20% of Yellow River sediment, 50-75% of bauxite tailings, the sum of the above raw materials is 100%, and 0.05-0.2% of cellulose ether and 7-15% of water are additionally added.
[0028] The waste residue alkali-activated material is prepared by mixing the following raw materials in the mass percentages: 35-45% of slag cement, 20-35% of red mud, 25-35% of fly ash, 0.02-0.06% of sodium hydroxide and 0.02-0.06% of sodium silicate.
[0029] The particle size range of the Yellow River sediment is 0.005mm-0.5mm, and the heavy metal leaching mass concentration of the sediment is lower than the national soil environmental quality standard GB15618. The particle size range of the coal gangue machine-made sand is 1.0mm-2.5mm. The aggregate particle size of the bauxite tailings is 4.75mm-9.5mm.
[0030] The application further provides a preparation method of the waste residue alkali-activated material solidified Yellow River sediment water permeable brick.
[0031] (1) Preparation of the mixing material of the upper layer water permeable brick: the waste residue alkali-activated material, the Yellow River sediment, the coal gangue machine-made sand, the water reducing agent and the water gel are weighed according to the proportion, are put into a mixer and are mixed uniformly, then water is added and is continuously mixed uniformly to obtain the mixing material of the upper layer water permeable brick;
[0032] (2) Preparation of the mixing material of the lower layer water permeable brick: the weighed waste residue alkali-activated material, the Yellow River sediment and the cellulose ether are pre-dry-mixed and mixed uniformly, then the bauxite tailings is added and is continuously mixed until uniform, finally water is added and is mixed uniformly to obtain the mixing material of the lower layer water permeable brick;
[0033] (3) Waste residue alkali-activated material solidified Yellow River sediment water permeable brick: first, the upper layer of mixed material is loaded into the mold and vibrated to be compacted; then, the lower layer of mixed material is continuously poured into the mold to fill the entire mold and vibrated to be compacted; wherein the filling volume ratio of the mixed material of the upper layer of water permeable brick to the mixed material of the lower layer of water permeable brick is 1:3; finally, the test piece with the mold is placed in an environment with a temperature of 20±2℃ and a relative humidity of 98% for 1d of curing, and then the mold is removed, and the test piece is taken out after curing for a corresponding age according to actual needs.
[0034] The technical solutions of the present application are further described below through examples.
[0035] The preparation process of the waste residue alkali-activated material used in the following examples is as follows: first, the red mud and fly ash are dried to constant weight and ground to a particle size of ≤35μm. Then, the treated red mud, fly ash and slag cement are mixed uniformly according to the mass fraction of 32%, 28% and 40% respectively to obtain dry mixture A, which is sealed and stored. Solid sodium hydroxide and sodium silicate are mixed in a ratio of 1:1 to obtain dry mixture B, which is sealed and stored. When used, dry mixture A and dry mixture B are mixed uniformly in a ratio of 25:1 to obtain the waste residue alkali-activated material.
[0036] Example 1
[0037] The present embodiment provides a waste residue alkali-activated material solidified Yellow River sediment water permeable brick. The raw materials used for the upper layer structure include waste residue alkali-activated material 25%, Yellow River alluvial sediment 15%, coal gangue machine-made sand 50%, hydrogel 10%, water reducing agent 0.2%, and water 12%. The raw materials used for the lower layer structure include waste residue alkali-activated material 25%, Yellow River alluvial sediment 20%, bauxite tailings 55%, cellulose ether 0.1%, and water 11%.
[0038] The preparation method is as follows: the waste residue alkali-activated material, Yellow River alluvial sediment, coal gangue machine-made sand, hydrogel and water reducing agent used for the upper layer structure of the water permeable brick are weighed according to the proportion, mixed uniformly in a mixer, and then water is added and continuously mixed uniformly to obtain the upper layer of mixed material. The waste residue alkali-activated material, Yellow River alluvial sediment and cellulose ether used for the lower layer structure are dry-mixed and mixed uniformly, and then bauxite tailings are added and continuously mixed until uniform, and finally water is added and mixed uniformly to obtain the lower layer of mixed material. Then, the upper layer of mixed material is first loaded into the mold and vibrated to be compacted, and then the lower layer of mixed material is continuously poured into the mold to fill the entire mold and vibrated to be compacted. The filling volume ratio of the upper layer of mixed material to the lower layer of mixed material is 1:3. Finally, the test piece with the mold is placed in an environment with a temperature of 20±2℃ and a relative humidity of 98% for 1d of curing, and then the mold is removed, and the test piece is taken out after curing for a corresponding age according to actual needs.
[0039] Example 2
[0040] The embodiment provides a waste residue alkali-activated material solidified Yellow River sediment water permeable brick, which comprises upper and lower layers.
[0041] The preparation method is the same as that in embodiment 1.
[0042] Embodiment 3
[0043] The embodiment provides a waste residue alkali-activated material solidified Yellow River sediment water permeable brick, wherein the raw materials for the upper layer structure comprise 20% of waste residue alkali-activated material, 16% of Yellow River silt, 56% of coal gangue machine-made sand, 8% of hydrogel, 0.15% of water reducing agent and 12% of water.
[0044] The preparation method is the same as that in embodiment 1.
[0045] The waste residue alkali-activated material solidified Yellow River sediment water permeable bricks prepared in the above embodiments 1-3 are subjected to performance tests, and the test results are shown in the following table.
[0046] Table 1 Performance of waste residue alkali-activated material solidified Yellow River sediment water permeable brick
[0047]
[0048]
[0049] It can be seen from the above test results that the waste residue alkali-activated material solidified Yellow River sediment water permeable brick prepared by the application has good water permeability and mechanical properties, and excellent frost resistance and wear resistance, and meets the standard requirements.
[0050] The above only describes the preferred embodiments of the application, and it should be noted that, for ordinary skilled persons in the art, several improvements and refinements can be made without departing from the principles of the application, and these improvements and refinements should also be regarded as the protection scope of the application.
Claims
1. A waste residue alkali-activated material solidified Yellow River sediment water permeable brick, characterized in that, The waste residue alkali-activated material solidified Yellow River sediment water permeable brick is a double-layer baking-free water permeable brick, comprising an upper layer water permeable brick with inconsistent pores and a lower layer water permeable brick, the upper layer water permeable brick has smaller pores than the lower layer water permeable brick, and the upper layer water permeable brick and the lower layer water permeable brick both contain waste residue alkali-activated material and Yellow River alluvial sediment.
2. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 1, characterized in that, The raw materials of the upper layer water permeable brick and the mass percentage thereof are as follows: 15-25% of waste residue alkali-activated material, 10-20% of Yellow River alluvial sediment, 45-65% of coal gangue machine-made sand, and 5-10% of water gel.
3. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 2, characterized in that, The upper layer water permeable brick additionally contains 0.15-0.20% of water reducing agent and 7-15% of water by mass percentage.
4. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 1, characterized in that, The raw materials of the lower layer water permeable brick and the mass percentage thereof are as follows: 15-30% of waste residue alkali-activated material, 10-20% of Yellow River alluvial sediment, and 50-75% of bauxite tailings.
5. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 1, characterized in that, The lower layer water permeable brick additionally contains 0.05-0.2% of cellulose ether and 7-15% of water by mass percentage.
6. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 1, characterized in that, The waste residue alkali-activated material is prepared by mixing raw materials in the following mass percentages: 35-45% of slag cement, 20-35% of red mud, 25-35% of fly ash, 0.02-0.06% of sodium hydroxide, and 0.02-0.06% of sodium silicate.
7. The waste residue-alkali activated material solidified Yellow River sand water permeable brick according to claim 1, characterized in that, The Yellow River alluvial sediment has a particle size range of 0.005-0.5 mm, and the heavy metal leaching concentration in the sediment is lower than the national soil environmental quality standard GB15618. 8.The waste residue-alkali activated material solidified Yellow River sediment water permeable brick according to claim 2, characterized in that, The coal gangue machine-made sand has a particle size range of 1.0-2.5 mm. 9.The waste residue-alkali activated material solidified Yellow River sediment water permeable brick according to claim 5, characterized in that, The aggregate particle size of the bauxite tailings is 4.75-9.5 mm.
10. A method for preparing the waste residue-alkali activated material solidified Yellow River sediment water permeable brick according to any one of claims 1-9, characterized in that, The method comprises the following steps: (1) Preparation of the mixing material of the upper layer water permeable brick: weigh the waste residue alkali-activated material, Yellow River alluvial sediment, coal gangue machine-made sand, water reducing agent, and water gel according to the proportions, put them into a mixer to mix uniformly, then add water and continue to mix uniformly to obtain the mixing material of the upper layer water permeable brick; (2) Preparation of the mixing material of the lower layer water permeable brick: mix the weighed waste residue alkali-activated material, Yellow River alluvial sediment, and cellulose ether uniformly in advance, then add the bauxite tailings and continue to mix until uniform, and finally add water and mix uniformly to obtain the mixing material of the lower layer water permeable brick; (3) Waste residue alkali-activated material solidified Yellow River sediment water permeable brick: first, fill the upper layer mixing material into a mold and vibrate to compact; then, continue to pour the lower layer mixing material to fill the entire mold and vibrate to compact; wherein the filling volume ratio of the mixing material of the upper layer water permeable brick to the mixing material of the lower layer water permeable brick is 1:3; finally, take out the test piece after 1 day of curing under the condition of a temperature of 20±2℃ and a relative humidity of 98%, and continue to cure according to the actual needs until the corresponding age.
Citation Information
Patent Citations
Double-layer baking-free permeable brick and manufacturing method thereof
CN101956357A
Water permeable bricks produced by using building waste residue and manufacturing method thereof
CN102418308A
Environment-friendly water permeable brick and preparation method thereof
CN112358255A
Sintered water permeable brick prepared from recycled aggregate with composite structure
CN113754461A
Aggregate formed by bonding Yellow River sediment as raw material at normal temperature and preparation method of aggregate
CN113880528A